Combining Optimized Particle Morphology with a Niobium‐Based Coating for Long Cycling‐Life, High‐Voltage Lithium‐Ion Batteries. Issue 13 (2nd June 2016) - Gabrielli, Giulio; Axmann, Peter; Diemant, Thomas; Behm, Rolf Jürgen; Wohlfahrt‐Mehrens, Margret
Abstract: Morphologically optimized LiNi0.5 Mn1.5 O4 (LMNO‐0) particles were treated with LiNbO3 to prepare a homogeneously coated material (LMNO‐Nb) as cathode in batteries. Graphite/LMNO‐Nb full cells present a twofold higher cycling life than cells assembled using uncoated LMNO‐0 (graphite/LMNO‐0 cell): Graphite/LMNO‐0 cells achieve 80 % of the initial capacity after more than 300 cycles whereas for graphite/LMNO‐Nb cells this is the case for more than 600 cycles. Impedance spectroscopy measurements reveal significantly lower film and charge‐transfer resistances for graphite/LMNO‐Nb cells than for graphite/LMNO‐0 cells during cycling. Reduced resistances suggest slower aging related to film thickening and increase of charge‐transfer resistances when using LMNO‐Nb cathodes. Tests at 45 °C confirm the good electrochemical performance of the investigated graphite/LMNO cells while the cycling stability of full cells is considerably lowered under these conditions. Abstract : One coat, two lifes : Morphologically optimized LiNi0.5 Mn1.5 O4 (LMNO‐0) is coated with a thin layer of LiNbO3 (LMNO‐Nb) using a simple and low‐temperature method. Full cells incorporating graphite anodes present a twofold higher cycling life when using the coated LMNO‐Nb as cathode material instead of the pristine LMNO‐0. The obtained results suggest improved cathode ‐material‐electrolyte interface and reduced aging during cycling when using LiNbO3 as coating material for LMNO.